Faktor-Faktor yang Mempengaruhi Consumer Decision Making Process (Studi Kasus Rumah Makan Bebek Sinjai Madura) - Rachmad Hidayat (Universitas Bunda Mulia, 2017)
The object of this study is RM Bebek Sinjay in Bangkalan Madura. The method used is the path analysis to see and analyze the variables model of consumer decision making process. The results showed that the purchasing decisions of consumers RM Bebek Sinjay accordance with the stages model of consumer decision making process. Variable problem recognition, information search, alternative evaluation and purchase decision has a significant influence in shaping the research model. Research variables have mutually reinforcing positive values in shaping the research model. RM Bebek Sinjay should consider the balance of the variables that make up the model of consumer decision making process if it is to retain its consumers. Recommended marketing strategy is to open new branches, improve product quality and service as well as improve product innovation.Keywords: Consumer decision making process, problem recognition, information search, alternative evaluation, path analysis and internal sources